Afranius de sexagenariis de ponte deiciendis - Szymański, Mikołaj (Symbolae Philologorum Posnaniensium Graecae et Latinae, 2023)
An attempt to reconstruct the wording of Afran. Repudiatus fr. 8 Ribbeck and to establish its function in the comedy.